Coming to Terms with Medical Terms – Exploring Insights from Native and Non-native English Speakers in Patient-physician Communication - Dahm, Maria (HERMES - Journal of Language and Communication in Business, 2012)
Using medical terminology involves a large risk of miscommunication in English-medium consultations as patients often do not know or misunderstand the terms commonly used by physicians, or even misuse terms in their interactions with medical professionals (Hadlow/Pitts 1991; Street 2003). Patients and physicians also frequently associate different meanings with the same medical terms, which further threatens patient-physician communication (Hadlow/Pitts 1991). To date most investigations on the impact of medical terminology have focused on native English speaking (NES) individuals in monolingual encounters, while insights from non-native English speaking (NNES) physicians and patients have been largely neglected. Through semi-structured interviews, this qualitative explorative study investigates the experiences of patients and physicians from diverse linguistic backgrounds in medical encounters within Australia. A particular focus is given to the way NES and NNES participants perceive and judge the impact of the meaning of medical terms on patient-physician communication. Findings suggest that both the use and meaning of medical terminology are perceived and judged very differently by individuals who come from different language backgrounds and who hold varying degrees of medical knowledge. Findings indicate that common blanket recommendations urging medical professionals to avoid or explain jargon may be futile since physicians and patient also diverge in their understanding of what constitutes jargon or medical terminology.